Corporate political activity in the context of sugar-sweetened beverage tax policy in the WHO European Region. (13th September 2022) - Lauber, Kathrin; Rippin, Holly; Wickramasinghe, Kremlin; Gilmore, Anna B
Abstract: Background: Sugar-sweetened beverage (SSB) taxes have emerged as an effective and increasingly popular tool to reduce added sugar intake, an important contributor to obesity and non-communicable diseases. A common barrier to the implementation of well-designed SSB taxes is the opposition of commercial actors. Focusing on the WHO European Region, this study seeks to map if and how key stakeholders have experienced industry efforts to influence SSB taxes. Methods: We identified 11 countries in the WHO European Region which have implemented SSB taxes or attempted to do so. Using an online survey informed by the global literature on industry interference with SSB taxation, we approached 70 in-country policymakers, advocates and academics. The data were analysed using an existing framework of corporate political activity. Results: Twenty-three experts from nine countries responded to the survey. Transnational SSB producers and their business associations were identified as the most active opponents of SSB taxation. Industry claims that the policy would have negative economic effects were identified as the most common and powerful arguments. Direct lobbying was reported in all study countries. Shifts in political activity were recognisable across stages of the policy process, moving from outright opposition to attempts to delay or weaken the policy after its announcement. Conclusion: Those seeking to introduce effective SSB taxation can use our findings to pre-empt and counter industry opposition. We identify several measures for preventing and mitigating industry interference with SSB tax policy.